2021
DOI: 10.3390/geosciences11060250
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Uranium Mining Impacts—A Review on Groundwater Remediation Technologies

Abstract: Groundwater contamination is one of the most concerning issues from uranium mining activities. Radionuclides cannot be destroyed or degraded, unlike some organic contaminants (and similar to metals). Besides, sites, where radionuclides may be found, are mainly radioactive and mixed waste disposal areas, and therefore many other contaminants may also be present in groundwater. The state-of-the-art of environmental technology is continually changing, and thus a review on technologies application is of utmost rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 65 publications
0
3
0
1
Order By: Relevance
“…Hence, in the past and recent research databases, we found a range of technologies (from conventional to advanced) available to treat arsenic/uranium-rich groundwater (Gandhi et al, 2022;Yadav et al, 2022). These technologies are based on various processes, such as ion exchange, membrane filtration, electrocoagulation, photocatalysis, adsorptions, co-precipitation and biological methods (Dinis and Fiúza, 2021).…”
Section: Technological Developments For Mitigating These Issuesmentioning
confidence: 99%
“…Hence, in the past and recent research databases, we found a range of technologies (from conventional to advanced) available to treat arsenic/uranium-rich groundwater (Gandhi et al, 2022;Yadav et al, 2022). These technologies are based on various processes, such as ion exchange, membrane filtration, electrocoagulation, photocatalysis, adsorptions, co-precipitation and biological methods (Dinis and Fiúza, 2021).…”
Section: Technological Developments For Mitigating These Issuesmentioning
confidence: 99%
“…Урановидобувні і переробні підприємства, споруджені на «світанку» ядерної ери в кінці 1940 -1950-х роках минулого століття, у багатьох випадках перетворилися на серйозні джерела радіоактивного і хімічного забруднення оточуючого гідрогеологічного середовища (Hu et al, 2010;NEA…, 2014;Romanchuk et al, 2020;Dinis, Fiúza, 2021), оскільки в той час бракувало практичного досвіду і часто була відсутня нормативна база для належного захисту людини і оточуючого середовища від небезпечних впливів радіоактивних компонентів і супутніх хімічних токсикантів, що властиві зазначеним об'єктам. До подібних радіаційно та екологічно небезпечних об'єктів належить колишнє виробниче об'єднання «Придніпровський хімічний завод» (ПХЗ), розташоване у промисловому передмісті м. Кам'янське (колишній Дніпродзержинськ) Дніпропетровської області.…”
Section: вступunclassified
“…However, implementing this method is a complex and expensive process. Moreover, its effectiveness depends on the hydrodynamic and geological parameters of the formation [14,15]. Reactive barriers are the most effective and least resource-consuming solution [16].…”
Section: Introductionmentioning
confidence: 99%